FLUORIDE INDUCED NEPHROTOXICITY: APOPTOSIS, ULTRASTRUCTURAL CHANGES AND RENAL TUBULAR INJURY IN EXPERIMENTAL ANIMALS - Quadri, *Javed Ahsan; Alam, Mohd. Meraj; Sarwar, Saba; Singh, Seema; Shariff, A; Das, Taposh K (International Journal of Ayurveda and Pharma Research, 2016)
Fluorosis is endemic in many countries across the globe. Most of the Indian states are endemic for fluorosis. Fluoride is known to cause many types of health complications and affects skeletal & soft tissues. The kidneys are one of the highly exposed organs for all the ingested toxins including fluoride. Therefore fluoride exposed subjects are highly vulnerable to fluoride induced nephrotoxicity. In recent years it has been demonstrated that the prevalence of renal impairment is remarkably high in different fluorosis endemic areas. Higher prevalence of CKD observed in central dry zone of Sri Lanka, a fluorosis endemic region. The prevalence of renal tubular dysfunctions is significantly high in residents of El Quel, which is also an endemic fluorosis area in Southern Algeria. On the basis of previous research reports it may be concluded that fluoride induces renal impairments and renal tubular injuries, cellular and sub-cellular ultrastructural changes. But all the research reports available are confined to animal models only. The data available on fluoride associated renal impairment in human is scant and limited to case reports and epidemiological studies. Due to the variation in types of animal models used in the studies, variations in quantity of fluoride administered and variations in route of fluoride administration, the generated insight cannot be translated to clinic. Therefore there is need to adopt a direct holistic approach to evaluate the adverse effects of fluoride on kidney structure and function in human subjects.